2019
DOI: 10.4103/aer.aer_118_19
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol infusion reduces blood loss and opiate consumption during fertility preserving myomectomy

Abstract: Objectives:The objective of this study is to evaluate the effect of esmolol-induced hypotensive anesthesia (EIHA) on intra-operative (IO) bleeding during open myomectomy.Patients and Methods:Eighty-eight women were randomly divided into the study group received EIHA without uterine tourniquet and control group who received normotensive anesthesia with uterine tourniquet. EIHA was provided as priming dose of esmolol (0.5 mg.kg-1) before the induction of anesthesia and esmolol infusion (0.05-0.3 mg.kg-1.min-1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…In addition, we find that esmolol can reduce intraoperative opioids dosage, which is consistent with the previous results of Hamed et al 22 What is more, it has also been proved that intraoperative infusion of esmolol can reduce postoperative opioid dosage in Gelineau study. 23 Esmolol itself has no analgesic effect, but some studies consider that its auxiliary analgesic effect is achieved through extending the effect of opioids.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we find that esmolol can reduce intraoperative opioids dosage, which is consistent with the previous results of Hamed et al 22 What is more, it has also been proved that intraoperative infusion of esmolol can reduce postoperative opioid dosage in Gelineau study. 23 Esmolol itself has no analgesic effect, but some studies consider that its auxiliary analgesic effect is achieved through extending the effect of opioids.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that esmolol, when used in continuous infusion, is effective in reducing undesirable hemodynamic effects such as hypertension and tachycardia during laryngoscopy maneuvers for orotacheal intubation [13][14][15]. Esmolol was also associated with lower intraoperative opioid consumption [16,17].…”
Section: Author Detailsmentioning
confidence: 99%